(untitled) (Academicia Globe: Inderscience Research, 2021)
We all know that today the fields of science, technology and education are developing faster than ever.Especially in our country, the president Shavkat Mirziyoyev has created great opportunities for young people to learn foreign languages. Several young people, who take advantage of the given opportunities,are gaining high places in world competitions. Today, the perfect study of foreign languages is of great importance for the further development of the country. It is a flat fact that languages play a crucial role in the efficiency of human communication and that the importance of them has been realized by more and more people, especially by linguists and experts in the foreign language teaching at home and abroad.